Meu tio Roseno, a cavalo: uma viagem memoriosa ao revés do tempo narrada pelo sobrinho que perscruta, remonta e conta as histórias do tio - Gularte, José Francisco Moreira (2021)
This dissertation aims to discuss the novel Meu tio Roseno, a cavalo (2000), by the writer Wilson Bueno, from Paraná (Brazil).We investigate some elements such as the narrator, memory and time by studying theoretical texts that approach the concepts from the quoted elements, as well as secondary literature about the work of the writer from Paraná. The work concerned talks about a travel in which the character Roseno tries to find his wife Doroí who is ready to give birth to Andradazil, their first daughter. The story of the traveling uncle is narrated by his nephew, although it happened before he was even born. The memories and stories from Roseno’s past overlap the chronological time of the story; these fragments from the past are later on gathered by the nephew who reconstructs and tells the memories of his uncle. After reading a substantial part of Wilson Bueno’s bibliography, we think the discussion of one of his main books is representative to contribute to the understanding of his complete oevre. The research is divided into three chapters. In the first one, we analyze relevant aspects to the narrator of the novel Meu tio Roseno, a cavalo, under the sight of the studies of the narrative, evidencing the aspects of the classical narrative and of the romance in the work. In the second chapter we engage ourselves into the study of memory, examining it as a restoring and reinterpreting element of the past, both in the work of fiction and in the historical facts related to the context of the novel. Lastly, the third chapter brings some analysis about the aesthetics of the novel Meu tio Roseno, a cavalo, which uses linguistics resources to give the narrative a picturesque appearance, besides using resources from the poetic text in the prose. As theoretical framework, the theoretical assumptions from Walter Benjamin, Ligia Chippini Moraes Leite, Silviano Santiago, Maurice Halbwachs, Jöel Candau, Jeanne Marie Gagnebin, Georges Didi-Huberman, among others are used.